Experimental and computational analysis of supramolecular motifs involving C-sp2(aromatic)-F and CF3 groups in organic solids - Panini, Piyush; Gonnade, Rajesh G.; Chopra, Deepak (New Journal of Chemistry, 2016)
A detailed experimental (SCXRD) and theoretical (PIXEL and QTAIM) investigation of the evolution of different supramolecular motifs formed via the presence of both C(sp(2))/(sp(3))-F groups in the crystal packing has been performed in a series of newly synthesized substituted benzanilides (containing ``both'' the fluorine and the trifluoromethyl group in the same molecule) along with previously reported similarly related crystal structures [CrystEngComm, 2008, 10, 54-67; CrystEngComm, 2012, 14, 1972-1989, CrystEngComm, 2013, 15, 3711-3733]. It was observed that the highest stabilized molecular motifs primarily consist of C(sp(2))-H center dot center dot center dot F-C(sp(2)) H-bonds in preference to C(sp(2))-H center dot center dot center dot F-C(sp(3)) H-bonds in the crystal. The motifs involving C(sp(2))-H center dot center dot center dot F-C(sp(2))/(sp(3)) H bonds were observed to be present over the entire distance range between 2.2 and 2.7 angstrom, albeit the difference in energies of stabilization involving fluorine atoms attached to sp(2) and sp(3) carbon is not significant in molecular crystals. From QTAIM analysis, the C(sp(2))/(sp(3))-F center dot center dot center dot F-C(sp(2))/(sp(3)) interactions were observed to be a closed shell in nature and provide local stabilization, indicating the formation of bonds, similar to weak hydrogen bonds observed in crystals.